(3QSGdI aj GdfghV hGdbjGe GdPi jYJGOg GdfGSs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3eSFdI ai GdfghV hGdbjGe GdPi jYJGOg GdfGS ef GdEcQGe hGdEMJQGe YfO bOhe TNU eYjf s
(3BNQgG (B:s
(3Cf gPG GdNVhY ddg JYGdi cGf MSfkG hjfhi HgeG eYfi LGFR hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs